Алгоритм вибору порядку інтерполяційного полінома при побудові нелінійної функції перетворення засобу вимірювань - Русанова, Є. В. (ХНУРЕ, 2021)
The problem of choosing the order of the interpolation polynomial for constructing the transformation function of measuring devices is considered. Increasing this parameter increases the accuracy of the approximation, but significantly increases the number of required calculations. A heuristic algorithm is proposed that provides a compromise between accuracy and computational complexity of the model. Modeling was performed using the system of engineering and scientific calculations MATLAB to study the proposed algorithm.